Methanol Synthesis from CO₂ and Hydrogenation over Cu-ZnO-black TiO₂ Catalysts: Effect of Copper Loading and ZnO Promotion - Chianese, Laura; Renda, Simona; Menéndez, Miguel; Iervolino, Giuseppina; Palma, Vincenzo; Vaiano, Vincenzo (Jornada de Jóvenes Investigadores del I3A, 2025)
The thesis focused on methanol synthesis from CO₂ and H₂ over Cu-ZnO-black TiO₂ catalysts with two different copper loadings (15 and 30 wt%). Additionally, the effect of ZnO addition on one of the catalysts was studied, evaluating its activity and selectivity under reaction conditions (WHSV:10h-1, Temperature: 180-300°C, Pressure:20 bar)